Digital Technology Characteristics and Literacy Among Families With Children With Asthma: Cross-Sectional Study - Kristin Kan; Lu Morales; Avani Shah; Emily Simmons; Leonardo Barrera; Liana Massey; Greta List; Ruchi S Gupta (JMIR Publications, 2023)
Abstract BackgroundThe use of digital technology in pediatric asthma management has emerged as a potential tool for improving asthma management. However, the use of digital tools has the potential to contribute to the inequitable delivery of asthma care because of existing social factors associated with asthma disparities. Our study focused on parents' chosen language and sociodemographic factors that might shape the use of digital technology in asthma self-management. ObjectiveThis study aims to estimate and compare patient, family, and technology-related characteristics by parents' chosen language (English or Spanish) and compare a digital literacy measure by sociodemographic factors. MethodsSurvey data were collected from July to December 2021 from parents of children with asthma who were seen by a Chicago pediatric health system pulmonary provider. Questions assessed patient and family characteristics, digital technology use, and digital literacy, measured using the validated eHealth Literacy Scale (eHEALS). Chi-square tests and multivariable logistic regression were used for comparisons, and Kruskal-Wallis tests were used for comparing median eHEALS scores by social characteristics. ResultsOf the 197 parents surveyed, 24.4% (n=49) of parents identified as a race categorized as other, 37.1% (n=67) as White, and 38.6% (n=75) as Black; 47.2% (n=93) identified as Hispanic/Latino/Latina. Additionally, 79.7% (n=157) of parents preferred English, and 20.3% (n=40) preferred Spanish. English-speaking parents were more likely to report having a data plan for their smartphone (117/157, 74.5%) or high-speed internet (138/157, 87.9%) compared to Spanish-speaking parents (smartphone: 23/40, 58%; PPPPPPP ConclusionsThe significant differences in technology-related characteristics suggest that digital connectivity, affordability, and data privacy may also be important factors in considering digital technology use in asthma care.